Nature of small tank cascade systems and a framework for rehabilitation of tanks within them - Sakthivadivel, Ramaswamy; Fernando, N.; Panabokke, Christopher R.; Wijayaratna, C.M. (International Irrigation Management Institute, 1996)
This report presents a methodology for planning the rehabilitation and improvement of small-scale irrigation systems within the context of the water basin when information on hydrology and water use is inadequate. It was developed for planning the rehabilitation and improvement of small tank systems in the dry zone of Sri Lanka. The methodology is useful to those undertaking irrigation rehabilitation projects in similar circumstances and it may also be extended to water resources planning in many other circumstances.